An analysis of the cost of disability across Europe using the standard of living approach - José-Ignacio Antón; Francisco-Javier Bra\~na; Rafael Mu\~noz de Bustillo (SERIEs - Journal of the Spanish Economic Association, 2016)
This article presents for the first time a comparative study of the cost of disability for households in 31 European countries. In order to do so, we exploit the European Union Statistics on Income and Living Conditions, its special module on housing conditions for 2007 and 2012 and employ two alternative methodologies, one based on how difficult it is for households to make ends meet and the other related to the access of households to a set of services and assets. The comparative nature of the present analysis shows these national estimates of the cost disability from a broader perspective than previous research. One important finding of this study is that there is a significant diversity in the cost of disability across European countries, with Scandinavian countries at the top of the ranking and Eastern European states at the bottom. We discuss some possible explanatory reasons for the pattern of costs across countries found in our analysis.
Keywords: I10; I30; 330; Disability; Cost; Standard of living; Income; Welfare